Long‐term Interest Rates and Public Debt Maturity. (8th April 2016) - Beetsma, Roel; Giuliodori, Massimo; Sakalauskaite, Ieva
Abstract : This paper adds to the literature studying how fiscal variables affect long‐term interest rates. Using a sample of sixteen OECD countries over the period 1980–2007, we show that a one‐year increase in the maturity of the public debt lowers the long‐term interest rate by on average 20–30 basis points. This negative effect is found for both static and panel vector autoregressive specifications. Country sample splits suggest that it is present in particular for low‐maturity or high‐inflation countries.